2020
DOI: 10.1101/2020.04.28.066696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptic plasticity induced by differential manipulation of tonic and phasic motoneurons in Drosophila

Abstract: 18Structural and functional plasticity induced by neuronal competition is a common feature of 19 developing nervous systems. However, the rules governing how postsynaptic cells differentiate 20 between presynaptic inputs are unclear. In this study we characterized synaptic interactions 21 following manipulations of Ib tonic or Is phasic glutamatergic motoneurons that co-innervate 22 Significance Statement 41Both invertebrate and vertebrate nervous systems display synaptic plasticity in response to 42 behaviora… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 156 publications
0
9
0
Order By: Relevance
“…Recently, new tools have been developed that enable electrophysiological isolation of MN-Is vs MN-Ib NMJs in Drosophila . In particular, GAL4 driver lines have been identified that enable selective expression in MN-Is or MN-Ib innervating muscle 6 (Aponte-Santiago et al, 2020; Carrillo-Reid et al, 2019; Pérez-Moreno & O’Kane, 2019). In addition, silencing of all neurotransmission from MN-Is or MN-Ib is now possible following the engineering of a botulinum neurotoxin (BoNT-C), which when selectively expressed in MN-Is or MN-Ib silences all neurotransmission without inducing heterosynaptic structural or functional plasticity at the convergent input (Han et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new tools have been developed that enable electrophysiological isolation of MN-Is vs MN-Ib NMJs in Drosophila . In particular, GAL4 driver lines have been identified that enable selective expression in MN-Is or MN-Ib innervating muscle 6 (Aponte-Santiago et al, 2020; Carrillo-Reid et al, 2019; Pérez-Moreno & O’Kane, 2019). In addition, silencing of all neurotransmission from MN-Is or MN-Ib is now possible following the engineering of a botulinum neurotoxin (BoNT-C), which when selectively expressed in MN-Is or MN-Ib silences all neurotransmission without inducing heterosynaptic structural or functional plasticity at the convergent input (Han et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…1 A ) (Hoang and Chiba, 2001). Functional differentiation has been demonstrated between terminal types (Kurdyak et al, 1994; Chouhan et al, 2010; Lu et al, 2016; Aponte-Santiago et al, 2020; He et al, 2022; Justs et al, 2022), and between type-Ib terminals on different muscle fibers (Chouhan et al, 2012; Newman et al, 2017; Wang et al, 2021; Justs et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Some groups have proposed there exist differences in how the synapse executes PHP at phasic vs. tonic motor terminals (Aponte-Santiago and Littleton, 2020, Genç and Davis, 2019, Newman et al, 2017, Sauvola et al, 2021), depending upon pharamacological vs. genetic challenge. Recent characterization of motor neuron-specific tools allow a refinement of analyses, at least in the context of presynaptic terminals (Han et al, 2022, Aponte-Santiago et al, 2020, Wang et al, 2021). For a second model, a recent study suggests that the type of pharmacological perturbation to glutamate receptors might control the eventual response (Nair et al, 2021).…”
Section: Discussionmentioning
confidence: 99%